2020
DOI: 10.1021/jacs.0c07153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Defects and H2O on the Hydrogenation of CO2 to Methanol over Pt Nanoparticles in UiO-67 Metal–Organic Framework

Abstract: In catalysts for CO 2 hydrogenation, the interface between metal nanoparticles (NPs) and the support material is of high importance for the activity and reaction selectivity. In Pt NP-containing UiO Zr-metal–organic frameworks (MOFs), key intermediates in methanol formation are adsorbed at open Zr-sites at the Pt–MOF interface. In this study, we investigate the dynamic role of the Zr-node and the influence of H 2 O on the CO 2 hydrogenation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 59 publications
(138 reference statements)
2
52
0
Order By: Relevance
“…Defective MOFs and their composites have received broad research interest in the eld of heterogeneous catalysis, including oxidation, 22,25,39,40,115,116 esterication, 27 CO 2 conversion, 36,81,117 and photo/electrocatalysis. 21,23,33,118 The CUSs and/or the actives species immobilized in the local microenvironment of structural defects can serve as active sites in different catalytic processes.…”
Section: Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…Defective MOFs and their composites have received broad research interest in the eld of heterogeneous catalysis, including oxidation, 22,25,39,40,115,116 esterication, 27 CO 2 conversion, 36,81,117 and photo/electrocatalysis. 21,23,33,118 The CUSs and/or the actives species immobilized in the local microenvironment of structural defects can serve as active sites in different catalytic processes.…”
Section: Catalysismentioning
confidence: 99%
“…121 Due to their high specic surface areas and hierarchical pores, defective MOFs enable reactant molecules to access the active sites even aer loaded with active guest species. 117 Different kinds of guest species, such as polyoxometalates (POMs) and metal nanoparticles (NPs) have been successfully incorporated into defective MOFs. [37][38][39]117,122,123 For example, Keggin-type POMs conned in defective UiO-66 were prepared via a one-pot method with an in situ addition of thiourea (Fig.…”
Section: Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies by Gutterød and co-workers 287 revealed that Pt@UiO-67 is catalytically competent for H 2 -based reduction of CO 2 , with the initial report describing formation of CO and the classic Sabatier reaction product, methane. Subsequent mechanistic 288 and structural studies, 289 including studies of the influence of missing-linker defects, permitted the reduction to be optimized for methanol production. The researchers found that the interfacial sites where Pt NPs and Zr nodes interact thus serve as the meeting point for formate produced at the node from zirconia-sorbed CO 2 and H atoms formed by dissociation of H 2 by Pt (Fig.…”
Section: Tuning Catalytic Activity and Selectivitymentioning
confidence: 99%
“…The high surface area generates a very high density of catalytic sites, allowing greater possibilities of contact with substrates and producing catalysts with high activity and excellent steric selectivity, tunable by changing linkers shape and length in the synthesis steps [178]. The range of reactions that can be performed with MOF-based catalysts is almost as wide as their synthetic tunability: industrially relevant reactions involving commodities production (butenes syntheses for synthetic rubber production) [181]; environmental remediation reactions with greenhouse gases abatement (CO 2 reduction through thermal- [182,183] or photo-catalytic processes [184]); photocatalytic [184] and electrocatalytic [185] hemi-reactions for fuel cells processes; and reactions for fine chemicals production [186]. Apart from these cases, there are only a few (yet remarkable) examples of MOFs employed as supports for catalysts employed as biomass valorization processer finalized to the production of higher added-value molecules.…”
Section: Metal Organic Frameworkmentioning
confidence: 99%